Pros And Cons Of Batuah Market Revitalization Banjarmasin City (Case Study Of Banjarmasin Mayor Decision Number 109 Of 2022) - Siti Kholisoh; Sulaiman Kurdi (Interdisciplinary Explorations in Research Journal, 2023)
Abstract This research was motivated by the Mayor of Banjarmasin issuing Decree Number 109 of 2022. When the Banjarmasin City government wanted to implement this decree, there was resistance from residents who live in Batuah Market, Banjarmasin City. However, traders who traded at Batuah Market just accepted the mayor's decree. Because Batuah Market is land owned by the regional government. This research aims to determine the background to the pros and cons of Batuah Market revitalization and the obstacles in revitalizing it, as well as the solutions provided by the Banjarmasin City Government to traders and residents of Batuah Market, Banjarmasin City. The type of research used is empirical legal research with a case study approach and analyzed using qualitative descriptive methods. Collecting data from informants through interviews and documentation. The research results show that the background to the pros and cons of Batuah Market revitalization is because there is no compensation given to residents who live in Batuah Market. Apart from that, the causes of conflict are differences in interests, socialization carried out by the government is not optimal and is not going well, and residents are threatened with losing the homes they have lived in for decades. Meanwhile, traders are pro for the revitalization of Batuah Market because there is a match between the government's wishes and traders' needs for market improvements. The obstacle in revitalizing it is the resistance from residents who live on the Batuah Market land. Then the solution given by the government to traders is to occupy the same place according to the type of merchandise. The solutions provided to residents include providing flats with free rental fees for one year, being given the opportunity to trade in government-owned markets, recruiting new entrepreneurs, providing educational tools from kindergartens to junior high schools. Keywords: Pros and Cons, Revitalization, Batuah Market Abstrak Penelitian ini dilatarbelakangi Walikota Banjarmasin menerbitkan Surat Keputusan Nomor 109 tahun 2022. Ketika pemerintah Kota Banjarmasin ingin mengimplementasikan surat keputusan tersebut, terjadi penolakan oleh warga yang bermukim di Pasar Batuah Kota Banjarmasin. Tetapi, pedagang yang berdagang di Pasar Batuah menerima saja terhadap surat keputusan walikota tersebut. Karena Pasar Batuah merupakan lahan milik Pemerintah daerah. Penelitian ini bertujuan untuk mengetahui latar belakang terjadinya pro dan kontra dalam revitalisasi Pasar Batuah dan kendalanya dalam merevitalisasi, serta solusi yang diberikan Pemerintah Kota Banjarmasin kepada pedagang dan warga Pasar Batuah Kota Banjarmasin. Jenis penelitian yang digunakan adalah penelitian hukum empiris dengan pendekatan studi kasus dan dianalisis dengan metode deskriptif kualitatif. Mengumpulkan data dari informan melalui wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa latar belakang terjadinya pro kontra revitalisasi Pasar Batuah karena tidak adanya ganti rugi yang diberikan kepada warga yang bermukim di Pasar Batuah. Selain itu, penyebab terjadinya konflik adalah perbedaan kepentingan, sosialisasi yang dilaksanakan oleh pemerintah tidak maksimal dan tidak berjalan dengan baik, dan warga terancam kehilangan tempat tinggal yang sudah dihuni puluhan tahun. Sedangkan pedagang yang pro terhadap revitalisasi Pasar Batuah karena adanya kesesuaian antara keinginan pemerintah dan kebutuhan pedagang akan perbaikan pasar. Adapun kendala dalam merevitalisasi adalah adanya penolakan dari warga yang bermukim di lahan Pasar Batuah. Kemudian solusi yang diberikan pemerintah kepada pedagang yaitu menempati tempat yang sama sesuai dengan jenis dagangannya. Adapun solusi yang diberikan kepada warga seperti diberikan hunian rumah susun digratiskan biaya sewa selama satu tahun, diberikan kesempatan untuk berdagang di pasar milik pemerintah, dijanjikan perekrutan wirausaha baru, bantuan alat pendidikan dari TK-SMP. Kata Kunci: Pro kontra, Revitalisasi, Pasar Batuah